Where the Caribbean is going with information technology. (1996)
Examines IT trends in Trinidad and Tobago, Barbados and Jamaica. Notes that the feeling among IT professionals today is that the most successful nations in the region will be those who build an effective information infrastructure to use and transport services, information and 'the new goods'.
DC